Book review Sustainable Diets - Linking nutrition and food systems - Cecil J. W. Meulenberg (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2019)
Book review Barbara Burlingame and Sandro Dernini (eds): SUSTAINABLE DIETS - LINKING NUTRITION AND FOOD SYSTEMS CAB International; 2019, 280 pages In the scope of the nutrition decade that started in 2016, this monograph addresses, in detail, the United Nations Food and Agriculture Organisation's current definition of sustainable diets from the perspective that 'those have low environmental impacts which contribute to food and nutrition security and to healthy life for present and future generations. Besides, are protective and respectful of biodiversity and ecosystems, culturally acceptale, accessible, economically fair and affordable; nutritionally adequate, safe and healthy; while optimizing natural and human resources.' Throughout 29 expert contributions, the current policy making process regarding the sustainable development goals of the United Nations General Assembly supported by the World Health Organisation and their implementation are explained in length.